In Search of Zärʾa Yaʿqob: A Study of the Philosophy and Intellectual History of the Ḥatäta Zärʾa Yaʿqob and the Debate Concerning its Authorship - Egid, Jonathan (Aethiopica, 2024)
Dissertation abstract